PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA MELALUI KEPUASAN KERJA PEGAWAI PT. BANK MANDIRI (PERSERO), TBK AREA JEMBER - Yunita Puspa Dewi; Diana Sulianti K Tobing; Sri Wahyu Lelly Hana Setyanti (RELASI : JURNAL EKONOMI, 2018)
The aim of this research is to understand the influence of transformational leadership, organizational culture, and organizational commitment toward employee’s performance through job satisfaction at PT. Bank Mandiri (Persero), Tbk and also to understand about direct and indirect effect all variables. This study used path analysis. The population of this research is all employees of officer-L5 Bank Mandiri Area Jember totaling 70 people. The sample in this research is 70 employees. The results showed that transformational leadership had a direct effect on job satisfaction of employees of Bank Mandiri Area Jember. Transformational leadership has a direct impact on the performance of Bank Mandiri employees in Area Jember. Organizational culture has a direct effect on job satisfaction of employees of Bank Mandiri Area Jember. Organizational culture directly affects the performance of employees of Bank Mandiri Area Jember. Organizational commitment has a direct effect on job satisfaction of employees of Bank Mandiri Area Jember. Organizational commitment has a direct effect on the performance of Bank Mandiri employees in Area Jember. Job satisfaction has a direct effect on the performance. Keywords : transformational leadership, organizational culture, organizational commitment, job satisfaction, employee’s performance, bank.